Stories from the field: Most Significant Change (MSC) synthesis - Harrington, Larry W.; Douthwaite, Boru; León, C. de; Woolley, Jonathan N. (CGIAR Challenge Program on Water and Food, 2008)
In January of 2007, a number of people working with the CGIAR Challenge Program on Water and Food (CPWF) were invited to tell stories about the “most significant change” (MSC) they had observed as a result of CPWF activity. They were guided by two questions, posed to establish the stories’ domain and time frame of interest. These were: “What has been the most significant technical development/advance made by your CPWF project / theme / basin since the start?” “What has been the most significant partnership change (significant in terms of making scientific progress and/or developmental impact more likely) that has taken place since the start of your CPWF project (or theme or basin)?” This paper aims to pull together some of the threads emerging from these stories, weaving them into a fabric that gives insight into CPWF approaches and achievements.